2003
DOI: 10.1037/0278-6133.22.5.513
|View full text |Cite
|
Sign up to set email alerts
|

The effects of widowhood on physical and mental health, health behaviors, and health outcomes: The Women's Health Initiative.

Abstract: This study examined whether widowhood was associated with physical and mental health, health behaviors, and health outcomes using a cross-sectional (N ϭ 72,247) and prospective (N ϭ 55,724) design in women aged 50 -79 years participating in the Women's Health Initiative observational study (85.4% White). At baseline, married women reported better physical and mental health and generally better health behaviors than widowed women. Whereas women who remained married over the 3-year period showed stability in men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
163
4
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(185 citation statements)
references
References 34 publications
12
163
4
6
Order By: Relevance
“…The mechanisms for increased susceptibility of widowed persons to CVD risk have been studied, and there is support for our observation that people who have experienced marital loss have a significantly higher prevalence of CVD risk factors than those who are or have never been married. [14] Wilcox et al [15] reported significant association between marital status and hypertension. September 2016, Vol.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms for increased susceptibility of widowed persons to CVD risk have been studied, and there is support for our observation that people who have experienced marital loss have a significantly higher prevalence of CVD risk factors than those who are or have never been married. [14] Wilcox et al [15] reported significant association between marital status and hypertension. September 2016, Vol.…”
Section: Discussionmentioning
confidence: 99%
“…These studies report high rates of depressive syndromes extending well beyond the first several months of bereavement. Overall, compared to non-bereaved controls, elevated rates of depression may last as long as 6 months (Bruce et al 1990;Thompson et al 1991), 9 months (Norris & Murrell, 1990), 18 months (Brent et al 1994), 2 years (Harlow et al 1991 b;Stroebe & Stroebe, 1991 ;Hays et al 1994 a, b;Carnelley et al 1999;Turvey et al 1999), 30 months , or even as long as 3 or more years (Bodnar & Kiecolt-Glaser, 1994;Mendes De Leon et al 1994 ;Lichtenstein et al 1996;Wilcox et al 2003). Thus, depressive symptoms whose onset occurs within the post-bereavement window of time the DSM uses to exclude the diagnosis of MDE appears to be as chronic and/or recurrent as SMD.…”
Section: Predictive Validators Diagnostic Consistency Over Timementioning
confidence: 99%
“…The stress experienced by widowed women exerts a negative impact on their psychological health (21). Furthermore, the resultant depression may last for many years after widowhood, which prolongs the adverse effects in older women (22,23).…”
Section: Discussionmentioning
confidence: 99%